An Analytical Study Of The Financial Performance Of A Luxury Hotel Startup In Southern Algeria: The Case Of The Golden Gazelle Hotel – Eloued, Algeria - Bougoffa, Mouhyddine; Korichi, Kheyreddine (جامعة الوادي - University of Eloued, 2020)
In this study we investigate the financial performance situation of the hotel service in a luxurious hotel in southern Algeria, through an analytical study by the measuring of profitability, liquidity, debt ratio in the period between 2013-2017. We have concluded that the profitability position shows an increasing trend till 2012. But in the last two years the ratio was negative because the hotel has recorded a deficit. While liquidity, is at highest level in 2010 and it begins a decreasing trend from till 2015. While, the Debt is at its lowest level in 2010, the ratio begins an increasing trend in 2011 and 2012 where records its highest level
مقال
Keywords: financial performance ; profitability ; liquidity ; hotel ; southern Algeria